Positive eWOM and Consumers with a Fear of Missing Out - Putri, Ni Luh Debby Maharani Eka; Sulhaini, Sulhaini; Saufi, Akhmad (International Research Journal of Business Studies, 2024)
The study aims at examing the effect of positive electronic word of mouth (eWOM) and consumers with Fear Of Missing Out (FOMO) of local skincare products. This research is quantitative in nature. the population are Indonesians who have shopped for local skincare products through s-commerce applications. the number of samples were 150. The data analysis is Structural Equation Modeling (SEM) approach, especially Partial Least Square (PLS) method.  The results showed that positive eWOM had no significant effect on impulse buying, while price discount showed the opposite. The study also found that  FOMO strengthens the effect of eWOM on impulse buying, suggesting that if the fear of missing out is high, positive eWOM prompts consumers to buy products impulsively.